Shock-driven formation of covalently bound carbon nanoparticles from ion collisions with clusters of C60 fullerenes. (April 2018) - Delaunay, R.; Gatchell, M.; Mika, A.; Domaracka, A.; Adoui, L.; Zettergren, H.; Cederquist, H.; Rousseau, P.; Huber, B.A.
Abstract: We show that the energetic processing of C60 clusters by slow atomic projectiles leads to ultrafast ( < ps ) formation of large covalent carbon nanoparticles containing a few hundreds of atoms. The underlying mechanism is found to be due to impulse-driven collisions between the projectile and the nuclei of the molecules. Experimental findings are well reproduced by classical molecular dynamics simulations. The cross sections for molecular growth processes forming covalent systems which contain more than 60 carbon atoms are about 5 ⋅ 10 − 14 cm 2 representing more than 70% of the geometrical cross sections. This demonstrates the high efficiency of the underlying processes. The formed carbon nanoparticles contain both aromatic and aliphatic structures which have also been considered as dust components in space. Graphical abstract: Image 1